A TIMM17A Regulatory Network Contributing to Breast Cancer - Cai, Jiajia; Chen, Jianyun; Huang, Ling; Wang, Changxi; Zhang, Weiyun; Zhou, Quan; Sun, Zhaohui (Frontiers in Genetics, 2021)
Background: Translocase of Inner Mitochondrial Membrane 17A (TIMM17A) is overexpressed in breast cancer (BRCA), and upregulation can increase the aggressiveness of BRCA cells. This study examined the influence of the TIMM17A gene network on BRCA outcome. Methods: Expression levels of TIMM17A were com BRCA is a highly heterogeneous clinical entity pared between normal and tumor tissues from the OncomineTM database, and the association with patient survival was analyzed using Kaplan-Meier Plotter. Clinical factors influencing TIMM17A expression were studied by UALCAN. Then, cBioPotal was used to identify genes interacting with TIMM17A, and network relationships were assessed using the R clusterProfiler package. The association between TIMM17A mutation and mRNA expression in BRCA was examined using the LinkFinder application in LinkedOmics, and co-expressed genes were assessed for functional enrichment using the LinkInterpreter application. Furthermore, TIMM17A expression correlation with cell cycle phase distribution was performed by flow cytometry. Finally, the target networks of kinases, miRNAs, and transcription factors were identified using GeneMANIA. The expression and correlation of potential miRNAs and targets were further validated in BRCA cell lines by qRT-PCR. Results: Expression of TIMM17A was significantly elevated in BRCA compared to normal tissue (P < 0.05), and overexpression was associated with both poor overall survival (OS) and shorter distant metastases-free survival (DMFS) (P < 0.05). Expression of TIMM17A was not associated with age, sex, BRCA subclass, clinical stage, or patient ethnicity. The co-expressed TIMM17A network was enriched in genes targeted by cell cycle regulators such as CDK1, miR-331, and E2F family transcription factors (FDR < 0.001). Expression of TIMM17A protein was correlated with CDK1 protein expression in BRCA cell lines as measured by western blotting. Furthermore, flow cytometry revealed a strong association between higher TIMM17A expression and faster cell cycle progression in these BRCA cell lines. Conclusion: Elevated TIMM17A expression accelerates the progression of BRCA, thereby reducing OS and DMFS. The TIMM17A-associated networks identified here provide clues to the molecular pathogenesis of BRCA and potential targets for BRCA treatment.